DEVELOPMENT AND STANDARDIZATION OF COMMUNICATION ADL (CADL) TEST FOR JAPANESE APHASIC PATIENTS - SUZUKI, Tsutomu; ITOH, Motonobu; TAKEUCHI, Aiko; TAKAHASHI, Machiko; ENDO, Kyoko; SASANUMA, Sumiko; WATAMORI, Toshiko; FUKUSAKO, Yohko (Rihabiritēshon igaku, 1987)
A measurement of functional communication ability in daily life called the ‘CADL’ has been developed and standerdized in Japan in cooperation with A. Holland of the University of Pittsburgh. The characteristics of this test lie in 1) the selection of test items in which the actual communication activities are sampled with considerations for extralinguistic context, and 2) the scoring system in which functionality is credited regardless of the response forms. Two hundred aphasic subjects and 40 normal subjects were tested with the CADL and the following results were obtained. 1) The validity of the CADL was tested first, by calculating the correlation coefficient between the CADL and the family questionnaire scores which reflected the aphasics' actual communication behavior at home, and second, by calculating the correlation coefficient between the CADL and the traditional aphasia test scores. Both yielded high correlation coefficient of 0.73 and 0.88 respectively, thus confirming the validity of the CADL. 2) The reliability of the CADL was confirmed by the high intertester reliability coefficient of 0.97, test-retest reliability coefficient of 0.96 and coefficient alpha of 0.94. 3) Consistently superior performance by normal subjects as well as a systematic drop in the CADL scores among the aphasic groups as a function of age was revealed. Our findings on the Japanese CADL as well as those from the US version indicate that functional communication tends to be more severely impaired in older than in younger aphasics. 4) A functional classification system based upon the total CADL score was proposed and proved to be a valid indicator of the level of aphasics' functional communication abilities in daily life. 5) The results of close analysis of the relationship between the CADL and the traditional aphasia test revealed that while the traditional aphasia test reflected linguistic impairment, the CADL reflected functional communication abilities.